Dependences of SMA mixture and its bituminous binder properties on bitumen batching system, mixing time and temperature on asphalt mixing plant - Bražiūnas, Justas; Sivilevičius, Henrikas; Virbickas, Romualdas (Journal of Civil Engineering and Management, 2013)
Bitumen holds the aggregate in hot mix asphalt (HMA). Without asphalt binder, HMA would simply be crushed stone or gravel. A bitumen batching system (BBS) is comprised of bitumen storage, transportation, weighing and discharge equipment in an asphalt mixing plant (AMP). The function of the equipment is to batch the binder heated up to working temperature and to discharge it into a mixer in batches. In the entire system, the binder is exposed to high temperature and oxygen. Bitumen is slowly oxidized when it is in contact with oxygen. The degree of oxidation is highly dependent on temperature, time and thickness of a bitumen film. This article models the key factors influencing on the dynamics of bitumen oxidation in BBS equipment. Stone mastic asphalt (SMA) mixture was produced from the same materials according to the same job-mix formula (JMF) in neighbouring batch type AMP by changing the mixing time of materials from 20 to 60 s. Bitumen binder was separated from the taken SMA samples and its gradation was identified. Thus, Marshall specimens were produced and tested. Penetration Pen25 of bitumen binder recovered in rotary evaporator, softening point Tsp was determined and penetration index Ip was calculated. The presented findings of experimental investigation show that the properties of bitumen binder in BBS working at two different technologies changed inconsistently. Due to gravitation, the bitumen intensively flowing into a mixer (BBS1) is impacted by oxidation more than the bitumen batched by a high-pressure pump (BBS2).